سوسيولوجية الحرية الدينية بين الاعتقاد والممارسة - بولزارق عبد الحفيظ (University of Eloued جامعة الوادي, 2024)
This article seeks to address the topic of the sociology of religious freedom within a contemporary approach, placing the concept within a cognitive context that traces Islamic specificity on one hand and Western pluralism of its laws on the other, leading to international law that is referred to in our contemporary time to interpret and legitimize the ritual worship practices of religions and laws, as well as the legitimacy of proselytizing campaigns targeting Islamic societies in their cultural identity. the article is an attempt, with a sociological spirit, to clarify the truth of the concept, its regulations, and its not being a concept foreign to our Islamic culture, as it is deeply rooted in it and has been ensured by its legislations and historical events during the time of the Prophet - peace be upon him - or during the time of the Companions, which is the best evidence of that. الملخص: يسعى هذا المقال إلى تناول موضوع سوسيولوجية الحرية الدينية في إطار مقاربة معاصرة، تضع المفهوم ضمن سياق معرفي تتبعي على أساس الخصوصيتين الإسلامية من جهة والغربية على تعدد شرائعها من جهة أخرى، وصولا إلى الشريعة الدولية التي يتم الاحتكام إليها في وقتنا المعاصر لتفسير وشرعنة الممارسات الطقوسية التعبدية للديانات والشرائع، وشرعنة حملات التنصير التي تستهدف المجتمعات الإسلامية في هويتها الحضارية. فالمقال محاولة استردادية بروح سوسيولوجية هدفها بيان حقيقة المفهوم وضوابطه وأنه ليس بالمفهوم الدخيل على ثقافتنا الإسلامية، بقدر ما هو أصيل بها وقد ضمنته بتشريعاتها والحوادث التاريخية في عهد الرسول -صلى الله عليه وسلم- أو في عهد الصحابة خير دليل على ذلك.
مقاربة معاصرة
Keywords: لحرية; الحرية الدينية; حرية المعتقد; التسامح; freedom; religious freedom; rituals; freedom of belief; tolerance